2008
DOI: 10.1126/science.1161299
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Changes of Neocortical Code for Associative Memory During Consolidation

Abstract: After learning, the medial prefrontal cortex (mPFC) gradually comes to modulate the expression of memories that initially depended on the hippocampus. We show that during this consolidation period, neural firing in the mPFC becomes selective for the acquired memories. After acquisition of memory associations, neuron populations in the mPFC of rats developed sustained activity during the interval between two paired stimuli, but reduced activity during the corresponding interval between two unpaired stimuli. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
170
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(195 citation statements)
references
References 27 publications
22
170
0
1
Order By: Relevance
“…Retention of long-but not short-term memory in certain types of associative learning has indeed been shown to require delayed synaptic changes in the mPFC (TakeharaNishiuchi et al, 2006;Takehara-Nishiuchi and McNaughton, 2008). This hypothesis is also consistent with the role of the mPFC in other studies, which show that mPFC is not required for primary learning but becomes essential when experimental conditions, such as CS-US contingencies, are reversed in a subsequent phase (Schoenbaum et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…Retention of long-but not short-term memory in certain types of associative learning has indeed been shown to require delayed synaptic changes in the mPFC (TakeharaNishiuchi et al, 2006;Takehara-Nishiuchi and McNaughton, 2008). This hypothesis is also consistent with the role of the mPFC in other studies, which show that mPFC is not required for primary learning but becomes essential when experimental conditions, such as CS-US contingencies, are reversed in a subsequent phase (Schoenbaum et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…These results confirm that the mPFC plays a key role in retrieving consolidated memories (Frankland and Bontempi, 2006;Takashima et al, 2006;Takehara-Nishiuchi and McNaughton, 2008). Additionally, since semantic congruency reflects the degree to which the newly learned information fits to preexisting knowledge (i.e., schema) (Kim et al, 2008), and given the assumption that such congruent information is more rapidly assimilated than information that does not fit a prior schema (Tse et al, 2007;van Kesteren et al, 2010), our data further support the view that such a fast track in memory consolidation might also be present in humans.…”
Section: Discussionsupporting
confidence: 74%
“…Along with its putative role in systems consolidation and retrieval (Maguire, 2001;Frankland and Bontempi, 2006;Takashima et al, 2006;Takehara-Nishiuchi and McNaughton, 2008), the mPFC has been indicated as a region involved in a diversity of functions, among which many with a mnemonic nature. The prefrontal cortex in general is believed to be involved in updating, maintenance, and manipulation of memory traces (Buckner and Wheeler, 2001;Fletcher and Henson, 2001), and the mPFC in particular is thought to be related to feeling of knowing (Kikyo et al, 2002), conceptual knowledge integration (Kumaran et al, 2009), perceptual matching (Summerfield and Koechlin, 2008), comprehension (Maguire et al, 1999;Mar, 2004), and remote associative memory (Takashima et al, 2007;Takehara-Nishiuchi and McNaughton, 2008), and is shown to actively replay learning-related neuronal spiking patterns during sleep (Takehara-Nishiuchi and McNaughton, 2008;Peyrache et al, 2009). Furthermore, mPFC lesions lead to specific retrieval impairments for remote, presumably consolidated memories (Takehara-Nishiuchi et al, 2006;Gilboa et al, 2009), and an absence of semantic congruency memory enhancement (Kan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several regions of the neocortex become more important for memory retrieval with the passage of time. Remote memory for context fear, spatial locations, and eyeblink conditioning requires the medial prefrontal cortex (Takehara et al 2003;Frankland et al 2004;Maviel et al 2004;Takehara-Nishiuchi and McNaughton 2008;TakeharaNishiuchi et al 2011), while socially transmitted food preferences depend on the oribitofrontal cortex (Lesburgueres et al 2011). Increased immediate early gene expression in the neocortex is also observed during remote memory retrieval in these tasks (Maviel et al 2004;Lesburgueres et al 2011).…”
Section: Animal Models Of Systems Consolidationmentioning
confidence: 99%